Exploiting the Autozygome to Support Previously Published Mendelian Gene-Disease Associations: An Update - Maddirevula, Sateesh; Shamseldin, Hanan E.; Sirr, Amy; AlAbdi, Lama; Lo, Russell S.; Ewida, Nour; Al-Qahtani, Mashael; Hashem, Mais; Abdulwahab, Firdous; Aboyousef, Omar; Kaya, Namik; Monies, Dorota; et al. (Frontiers in Genetics, 2020)
There is a growing interest in standardizing gene-disease associations for the purpose of facilitating the proper classification of variants in the context of Mendelian diseases. One key line of evidence is the independent observation of pathogenic variants in unrelated individuals with similar phenotypes. Here, we expand on our previous effort to exploit the power of autozygosity to produce homozygous pathogenic variants that are otherwise very difficult to encounter in the homozygous state due to their rarity. The identification of such variants in genes with only tentative associations to Mendelian diseases can add to the existing evidence when observed in the context of compatible phenotypes. In this study, we report 20 homozygous variants in 18 genes (ADAMTS18, ARNT2, ASTN1, C3, DMBX1, DUT, GABRB3, GM2A, KIF12, LOXL3, NUP160, PTRHD1, RAP1GDS1, RHOBTB2, SIGMAR1, SPAST, TENM3 and WASHC5) that satisfy the ACMG classification for pathogenic/likely pathogenic if the involved genes had confirmed rather than tentative links to diseases. These variants were selected because they were truncating, founder with compelling segregation or supported by robust functional assays as with the DUT variant that we present its validation using yeast model. Our findings support the previously reported disease associations for these genes and represent a step towards their confirmation.